Многозначность смыслового плана аллегории в романе Спироса Пласковитиса «Плотина» - Банах, Л.С. (Культура народов Причерноморья, 2013)
В статье впервые в отечественном литературоведении предлагаются различные
интерпретации смыслового плана аллегории в романе Спироса Пласковитиса «Плотина», исследование
проводится при помощи типологического, социологического, сравнительного, герменевтического
подходов и метода символической интерпретации
Ключевые слова: новогреческая литература, аллегория, смысловой план В статті вперше у вітчизняному літературознавстві пропонуються різні інтерпретації
семантичного плану алегорії в романі С. Пласковітіса «Гребля», дослідження проводиться за
допомогою типологічного, соціологічного, порівняльного, герменевтичного підходів та методу
символічної інтерпретації
Ключові слова: новогрецька література, алегорія, семантичний план The Greek writers, representatives of the so called “generation of the 60th” used allegory as the main
type of imagery in their novels. The novel “The Dam” (1960) by Spyros Plaskovitis became the outstanding
creative work of the decade. In this article for the first time in the Ukrainian criticism of literature the different
interpretations of the semantic plan of allegory in the novel “The Dam” by Spyros Plaskovitis are proposed,
such as political, ecological, existential allegory. The relationships between the authorities, the population and
the dam in the novel reflect the social and political events of the 50-60th years of the XX-th century in Greece.
The novel has the “ecological” semantic plan, which shows the problems of the dangerous conflict between the
nature and the human beings. Besides, the existential questions about the sense of life and attitude to death, the
theme of the sin, the blame and the responsibility for the existence of the other people. The dam is also regarded
as the internal barrier in the psychological world of the main character. The semantic parallel with the novel
“The Plague” by Albert Camus is done on the thematic and problematic levels, in the depiction of the main
character and the place of action. The research is done with the help of typological, sociological, comparative,
germenetical approaches and of the method of symbolical interpretation
Key words: New Greek prose, allegory, the semantic plan